Elastyczność cenowa popytu na drewno sosnowe sprzedawane na rynku detalicznym surowca drzewnego na przykładzie RDLP w Zielonej Górze - Adamowicz, Krzysztof; Cierniak, Natalia (Leśne Prace Badawcze, 2011)
This paper presents the results of analyses of the pinewood trade on the retail timber market for 20 forest districts situated within the administrative boundary of the Regional Directorate of State Forests in Zielona Góra. Changes in 1995–2005 in the demand for three basic timber types sold on the retail timber market as well as the dynamics of their prices and volume are presented. In the analyzed period, demand for the medium-size timber was elastic and for small-size timber – constant. The sales volume of wood was determined by the price level for each timber assortment. The timber market is characterized by a low elasticity.